2015
DOI: 10.1242/dev.111997
|View full text |Cite
|
Sign up to set email alerts
|

Snail2/Slug cooperates with Polycomb repressive complex 2 (PRC2) to regulate neural crest development

Abstract: Neural crest cells arise from the border of the neural plate and epidermal ectoderm, migrate extensively and differentiate into diverse cell types during vertebrate embryogenesis. Although much has been learnt about growth factor signals and gene regulatory networks that regulate neural crest development, limited information is available on how epigenetic mechanisms control this process. In this study, we show that Polycomb repressive complex 2 (PRC2) cooperates with the transcription factor Snail2/Slug to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 69 publications
1
56
1
Order By: Relevance
“…EZH2 has been considered an essential factor for epigenetic regulation of E-cadherin [43]. Binding of PRC2 members, such as EZH2, Suz12, and EED, to the promoter of target gene induces epigenetic regulation that is regulated by Snail, which cooperates with PRC2 [43, 52, 70, 71]. Snail is also required for EZH2-mediated E-cadherin repression and the complex of EZH2/HDAC/Snail contributed to E-cadherin silencing in carcinomas [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 has been considered an essential factor for epigenetic regulation of E-cadherin [43]. Binding of PRC2 members, such as EZH2, Suz12, and EED, to the promoter of target gene induces epigenetic regulation that is regulated by Snail, which cooperates with PRC2 [43, 52, 70, 71]. Snail is also required for EZH2-mediated E-cadherin repression and the complex of EZH2/HDAC/Snail contributed to E-cadherin silencing in carcinomas [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 directly interacts with β-catenin [73], DNMT1, DNMT3A, DNMT3B [74], EED [58], ERÎą [73], GATA4 [69], NF-ÎşB [75], PCNAassociated factor (KIAA0101) [76], SNAI2 (Slug) [77] and SUZ12 [58]. Although the mechanisms underlying these interactions remain unclear, EZH2 also interacts with the androgen receptor (AR) [78], ASXL1 [79], FOXP3 [80] and REST [81].…”
Section: Ezh2 Mll3 and Nsds As Rational Drug Targetsmentioning
confidence: 99%
“…CDKN2A repression subsequently leads to EZH2 upregulation through CDK4/6-mediated E2F activation; these events constitute the E2F/ EZH2 positive-feedback loop. EZH2 also interacts with SNAI2 to repress the CDH1 gene, which encodes E-cadherin [77]. EZH2 also interacts with other non-PRC2 proteins to transcriptionally activate the target genes of the β-catenin-TCF/LEF complex (MYC and CCND1, among others) [73,76] and of NF-ÎşB (IL-6, TNF, NOTCH1, among others) [75,85].…”
Section: Ezh2 Mll3 and Nsds As Rational Drug Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been described the opposite function of the two isoforms of AEBP2 (DNA-binding repressor for the aP2) on PCR2 expression and, consequently, on neural crest cell migration during development (Kim et al, 2015). Likewise, it has been also shown that Snail/Slug cooperates with PRC2 in the regulation of NCCs development (Tien et al, 2015).…”
Section: Polycomb Repressive (Prc)mentioning
confidence: 99%